The endosymbiont Wolbachia rebounds following antibiotic treatment. - Emma L Gunderson; Ian Vogel; Laura Chappell; Christina A Bulman; K C Lim; Mona Luo; Jeffrey D Whitman; Chris Franklin; Young-Jun Choi; Emilie Lefoulon; Travis Clark; Brenda Beerntsen; et al. (PLoS Pathogens)
Antibiotic treatment has emerged as a promising strategy to sterilize and kill filarial nematodes due to their dependence on their endosymbiotic bacteria, Wolbachia. Several studies have shown that novel and FDA-approved antibiotics are efficacious at depleting the filarial nematodes of their endosymbiont, thus reducing female fecundity. However, it remains unclear if antibiotics can permanently deplete Wolbachia and cause sterility for the lifespan of the adult worms. Concerns about resistance arising from mass drug administration necessitate a careful exploration of potential Wolbachia recrudescence. In the present study, we investigated the long-term effects of the FDA-approved antibiotic, rifampicin, in the Brugia pahangi jird model of infection. Initially, rifampicin treatment depleted Wolbachia in adult worms and simultaneously impaired female worm fecundity. However, during an 8-month washout period, Wolbachia titers rebounded and embryogenesis returned to normal. Genome sequence analyses of Wolbachia revealed that despite the population bottleneck and recovery, no genetic changes occurred that could account for the rebound. Clusters of densely packed Wolbachia within the worm's ovarian tissues were observed by confocal microscopy and remained in worms treated with rifampicin, suggesting that they may serve as privileged sites that allow Wolbachia to persist in worms while treated with antibiotic. To our knowledge, these clusters have not been previously described and may be the source of the Wolbachia rebound.